Virus-induced airway hyperresponsiveness in guinea pigs is related to a deficiency in nitric oxide. - Folkerts, G (1995)
Intratracheal inoculation of parainfluenza type 3 virus to guinea pigs induces a marked increase in airway responsiveness in vivo and in vitro. In spontaneously breathing anesthetized guinea pigs inhalation of an aerosol containing the nitric oxide (NO) precursor L-arginine (2.0 mM) completely prevented the virus-induced airway hyperresponsiveness to histamine. In addition, perfusion of L-arginine (200 microM) or the direct NO-donor S-nitroso-N-acetyl-penicillamine (SNAP, 1 microM) through the lumen of tracheal tubes from infected animals prevented the increase in airway responsiveness to histamine or the cholinoceptor agonist methacholine. The NO synthase inhibitor N omega-nitro-L-arginine methyl ester (L-NAME, 120 microM) did not further increase the virus-induced airway hyperresponsiveness. In additional experiments, NO was measured with an Iso-NO nitric oxide meter and sensor. Stimulation of control tissues in vitro with histamine (10(-3) M) resulted in a contraction with a simultaneous release of NO (44.5 +/- 5.4 nM). The release of NO was markedly reduced by 75% (P < 0.01, 11.4 +/- 3.1 nM) in tracheas from virus-infected animals that demonstrated enhanced contractile responses. Preincubation of tissues from virus-treated guinea pigs with L-arginine (200 microM) completely prevented the enhanced contraction and simultaneously returned the NO production to control values (51.2 +/- 3.4 nM). An NO deficiency might be causally related to the development of airway hyperresponsiveness after a viral respiratory infection.